Factors affecting knowledge transfer and absorptive capacity in multinational corporations - Choong, Y. Lee; Fang, Chi Wu (2006)
With the increasing speed of competition, knowledge management has become a critical competitive weapon.The process of knowledge transfer between business units is an essential aspect of knowledge management.The ability to transfer knowledge internally is one of the main competitive advantages of multinational corporations.In this paper we will explore knowledge transfer and absorptive capacity in multinational corporations. Were view relevant literature on knowledge management especially for knowledge transfer and absorptive capacity. The objective of our study is two fold.First, conceptualize of absorptive capacity by emphasizing both ability and motivation.Second, explore the internal transfer of knowledge by multinational corporations.Based on the literature review, the absorptive capacity of the receiving unit is the most critical determinant of internal knowledge transfer in MNCs (Gupta and Govindarajan, 2000). However, the existing literature on absorptive capacity often do not capturing the various facets of absorptive capacity. We suggest that absorptive capacity should be comprised of both employees’ ability and motivation. Both ability and motivation can facilitate knowledge transfer from other parts of the MNC. Also, we expect to discover that the absorptive capacity of the subsidiary facilitates transfer of knowledge from other parts of the multinational corporations.